Human genetics: international projects and personalized medicine - Apellaniz-Ruiz, Maria; Gallego, Cristina; Ruiz-Pinto, Sara; Carracedo, Angel; Rodríguez-Antona, Cristina (Drug metabolism and drug interactions, 2016)
In this article, we present the progress driven by the recent technological advances and new revolutionary massive sequencing technologies in the field of human genetics. We discuss this knowledge in relation with drug response prediction, from the germline genetic variation compiled in the 1000 Genomes Project or in the Genotype-Tissue Expression project, to the phenome-genome archives, the international cancer projects, such as The Cancer Genome Atlas or the International Cancer Genome Consortium, and the epigenetic variation and its influence in gene expression, including the regulation of drug metabolism. This review is based on the lectures presented by the speakers of the Symposium “Human Genetics: International Projects & New Technologies” from the VII Conference of the Spanish Pharmacogenetics and Pharmacogenomics Society, held on the 20th and 21st of April 2015.